THE FACTORS AFFECTING EFFECTIVE ORGANIZATIONAL CULTURE MANAGEMENT: A CASE STUDY HONGFU COMPANY IN CHINA: - - Dongjie, Zhan; Wongkumchai, Tachakorn; Worapongpat, Ntapat (The Journal of International Buddhist Studies College, 2024)
The primary objective of this research is twofold. Firstly, it aims to discern the various factors that influence the efficient management of organizational culture in the context of environmental protection for recycled plastic products. Secondly, it strives to formulate a comprehensive model for effectively managing the organizational culture of such environmentally conscious recycled plastic products. In order to accomplish these objectives, the research employs a quantitative research methodology. A total of 172 individuals were selected as the sample size from a population of 300 individuals, which comprised general managers, internal staff, distributors, and competitors in the distribution market. The sampling method employed for this research was the well-known Yamane Taro technique. The data collection process was facilitated through the administration of a questionnaire, which exhibited a commendable reliability coefficient (IOC) of 0.81. Various statistical methods were utilized to analyze the collected data, including IOC, Average, Standard Deviation, Pearson correlation, and Multiple Regression Analysis. The outcomes of the investigation have revealed a series of noteworthy findings. Firstly, it has been observed that the collaboration between individuals and organizations plays a crucial role in various aspects. This includes the enhancement of industry competition, the adaptation to market environment, and the improvement of employee participation and work efficiency. Furthermore, the study has identified that the utilization of indicators and awards positively affects organizational structure and communication model. Moving on to the second point, the research has established that the management model for environmentally friendly recycled plastic products has a significant impact on the effective management of organizational culture. This impact has been measured quantitatively, with an effect size of 31.10 percent. This finding implies that organizations that adopt this management model are more likely to successfully cultivate and maintain a positive and sustainable organizational culture. Therefore, it is recommended that organizations consider implementing this management model to optimize their cultural management strategies and achieve long-term success. In conclusion, the research has shed light on the importance of collaboration, indicators, awards, and the management of environmentally friendly recycled plastic products in enhancing organizational culture and overall effectiveness.